(untitled) (Bangladesh Journal of Plant Taxonomy, 2023)
The present article deals with recording ethnomedicinal plants used by the people living in and around Dhaka city and also focuses on the plant species used during the pandemic to get relief from COVID-19. The information was gathered using open-ended and semi-structured questionnaires from 348 informants belonging to different classes of life. The survey has resulted in the recording of a total of 160 medicinal plant species belonging to 62 families and used for 157 ailments through 250 different formularies. Azadirachta indica A. Juss. was the most cited species in the study area. The highest factor informant consensus (FIC) was found in the Cuts and Wounds category, and Cynodon dactylon (L.) Pers. is the most cited species for this category. Acmella calva (DC.) R.K. Jansen was the culturally bound species attaining 100% Fidelity Level (FL) value. Among the ethnomedicinal plants, 40 species were found in the survey that were used by people to get relief from COVID-19. This interesting ethnomedicinal use is a new record for these 40 species. Most notable species are (Ocimum tenuiflorum L., Justicia adhatoda L., Centella asiatica (L.) Urban, Citrus aurantifolia (Christm. & Panzer) Swingle, Syzygium aromaticum (L.) Merr. & L.M. Perry, Mentha arvensis L., Zingiber officinale Rosc., Camellia sinensis (L.) O. Kuntze, and Nigella sativaL.Since ancient times, these species have been very popular and used to treat several ailments. The use of these species during the pandemic is a new hope to get relief from COVID-19 but this is very preliminary report. Further long-term study is needed to confirm the claim of these plants’ use against COVID-19. Due to excessive use during COVID-19, these species are very rare in the habitats in and around Dhaka city. Conservation measures should be applied to save these species from extinction. Bangladesh J. Plant Taxon. 30(1): 123-151, 2023 (June)